Analysis of the Influence of Leadership, Organizational Culture, Occupational Safety and Health on Employee Performance through Work Motivation as a Moderation Variable at PT Pelindo Regional I Dumai Branch - Chandra Hidayat; M. Chaerul Rizky; Yohny Anwar (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of leadership, organizational culture, and occupational safety and health on employee performance through work motivation as a moderation variable at PT Pelindo Regional I Dumai Branch. The background of this research is based on the importance of the role of leadership and organizational culture in creating a conducive work environment and the implementation of a good occupational safety and health (K3) system to improve employee performance. This type of research is quantitative research with a survey approach. The population in this study is 35 employees of PT Pelindo Regional I Dumai Branch, with sampling techniques using the census method. Data collection was carried out through the distribution of questionnaires and data analysis using the SmartPLS version 4 tool. The results of the study show that leadership has a positive and significant effect on employee performance and is the most dominant factor in improving employee performance. Occupational safety and health also have a positive and significant effect on employee performance, as well as work motivation which has been proven to have a significant positive effect. However, organizational culture does not have a significant effect on employee performance, indicating that organizational cultural values have not been well internalized in work practices. In mediation testing, work motivation was shown to be able to mediate the influence of leadership on employee performance, but it was unable to mediate the influence of organizational culture and occupational safety and health on employee performance.